Estudo de caso: resposta do milho a doses e fracionamento do nitrogênio - Reis, Jonas Rafael (2018)
Since the antiquity in agriculture, yield increase has been conditioned by the use of new techniques derived from increasing man's knowledge. In recent farming is not different, that is, in times of precision farming these techniques are even more evident in the most diverse crops. What has been verified in the last years in the corn crop is the possibility that the more recent hybrids can response to the nitrogen management with late application, especilly at the time of flowering of the crop, probably influencing positively the final grain weight and improving the yield. For this, a work was developed in a field located in the countryside of the city of Carazinho-RS, with the hybrid "AGROCERES 9025 PRO3®". The area selected for the work was selected using yield maps trough yield monitor and Electrical Conductivity map provided through Veris CE® to attest the homogeneous condition for both treatments. The treatment 1 (T1) used by the farmer consisted of 180 kg / ha of Nitrogen (N) in the form of urea in 3 doses: 54 kg / ha in V4, 63 kg / ha in V6 and 63 kg / ha in V8. The treatment 2 (T2) was 54 kg / ha in V4, 81 kg / ha in V6, 0 kg / ha in V8 and 45 kg / ha in VT. The applications were carried out with the machine called "Imperador 3.0" that had a hydraulic system that allows the machine to increase the soil clearance in 40 cm, allowing this late application. To verify the results, yield maps were used using mass flow sensors installed in the farmer's combine. With these files it was verified that the yield in the proposed treatment presented a positive response in relation to the treatment of the farmer.